Imagine yourself as a little girl…—efficacy and psychophysiology of imagery techniques targeting adverse autobiographical childhood experiences- multi-arm randomised controlled trial - Bączek, Julia; Karkosz, Stanisław; Pietruch, Magdalena; Szymański, Robert; Michałowski, Jarosław M. (Frontiers in Psychology, 2026)
Fear of failure is often rooted in highly self-critical autobiographical memories that elicit persistent distress and avoidance. Imagery-based interventions aim to reduce the impact of such memories, yet their mechanisms of action remain unclear. In this three-arm parallel group randomised controlled trial, 180 young adults with elevated fear of failure were randomly assigned to imagery exposure, standard imagery rescripting, or imagery rescripting with a 10-min delay designed to disrupt memory reconsolidation. Across four sessions delivered over 2 weeks, outcomes were assessed using self-report measures and physiological markers, with follow-ups at 3 and 6 months. All interventions led to significant and sustained reductions in negative emotions, arousal, and fear of failure, as well as decreased physiological reactivity to autobiographical memories of criticism. Contrary to predictions, delayed rescripting did not show superiority, while planned contrasts suggested more consistent benefits of standard rescripting compared to delayed rescripting and a rebound effect after exposure. Notably, prediction error, operationalised as transient increases in physiological arousal during rescripting, predicted stronger therapeutic change in rescripting but not in exposure. These findings demonstrate that both common therapeutic factors and prediction error contribute to durable improvements in emotional responses to adverse memories, advancing the understanding of mechanisms underlying imagery-based techniques.Clinical trials registrationClinicalTrials.gov Identifier: NCT07048756, https://clinicaltrials.gov/ct2/show/NCT07048756.